2012
DOI: 10.1016/j.healthplace.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

School sport policy and school-based physical activity environments and their association with observed physical activity in middle school children

Abstract: Empirical research on the effects of school sport policies on children's physical activity is limited. This study examined sport policies (intramural vs. varsity), physical settings within schools, and supervision in relation to physical activity using the System for Observing Play and Leisure in Youth (SOPLAY). Data were collected on physical activity levels of children in four middle schools. Regression analyses assessed the main effects of sport policy, type of physical activity setting, and supervision as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 47 publications
4
39
1
1
Order By: Relevance
“…This finding is also somewhat expected as most IS sports have limited teams and spaces for students whereas IM sports accept all students who want to play. Furthermore, when combined with previous research, that boys exhibit higher physical activity levels in intramurals than interscholastic sports [20], these findings also suggest intramurals may be more effective than traditional interscholastic sports at increasing daily physical activity levels among middle school children.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This finding is also somewhat expected as most IS sports have limited teams and spaces for students whereas IM sports accept all students who want to play. Furthermore, when combined with previous research, that boys exhibit higher physical activity levels in intramurals than interscholastic sports [20], these findings also suggest intramurals may be more effective than traditional interscholastic sports at increasing daily physical activity levels among middle school children.…”
Section: Discussionsupporting
confidence: 69%
“…These alternatives facilitate opportunities for more children to participate in sport and introduce children from diverse backgrounds to a wider variety of sports. For example, a recent study found that intramurals are associated with higher physical activity levels than interscholastic sports for boys [20]. Furthermore, exposure to different types of sports nurtures a sense of competence and enjoyment that last beyond a child's school years [18] and can set adult lifestyle patterns [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…So there is a critical need to arrange for the availability of a regular physical activity in schools specially that children spend most of their daily hours at school [42]. However, in our study there was no significant role for sport practice in development of overweight or obesity in children.…”
Section: Discussioncontrasting
confidence: 59%
“…11 This study was designed and analysed as a nested cross-sectional study with a pre to post-test control group design. To account for the clustered (or nested) nature of the data within each school the data was analysed using a linear mixed model (PROC MIXED in SAS V 9.2, SAS Inc Cary NC), 14 where treatment group within school was modelled as a random effect. The analysis adjusted for differences between schools at baseline.…”
Section: Methodsmentioning
confidence: 99%